Design, Synthesis and Evaluation of Novel 1,4-Disubstituted Piperazine-2,5-dione Derivatives as Antioxidants against H2O2-Induced Oxidative Injury via the IL-6/Nrf2 Loop Pathway - Liang Xiong; Hongshan Wu; Ting Zhong; Fang Luo; Qing Li; Mei Li; Yanhua Fan (MDPI AG, 2022)
Excessive reactive oxygen species (ROS) production leads to oxidative stress in cells, impairing the function of mitochondria and finally inducing cell apoptosis. Considering the essential role of oxidative stress in the pathogenesis of various neurodegenerative diseases and psychiatric disorders, the discovery of novel antioxidants has attracted increasing attention. Herein, a series of novel 1,4-disubstituted piperazine-2,5-dione derivatives were designed, synthesized and evaluated for their antioxidative activity. The results of the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) assay indicated that none of the tested compounds showed significant toxicity to SH-SY5Y cells at concentrations up to 80 μM. Cell counting via flow cytometry revealed that most of the tested compounds could effectively protect SH-SY5Y cells from H2O2-induced oxidative damage at 20 μM. Among these compounds, compound 9r exhibited the best antioxidative activity. Further mechanistic investigation indicated that 9r decreased ROS production and stabilized the mitochondrial membrane potential to restrain cell apoptosis, and promoted cell survival via an IL-6/Nrf2 positive-feedback loop. These results suggested the potential of compound 9r as a novel antioxidative candidate for the treatment of diseases caused by oxidative stress.